2016
DOI: 10.18006/2016.4(5s).564.571
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of peanut (Arachis hypogaea L.) seed oil and fatty acids composition under different growing season under mediterranean environment

Abstract: KEYWORDS Arachis hypogeal Fatty acid Growing season Iodine value Oleic linoleic acid ABSTRACTPeanut is one of the most important oil and protein producing crops in the world. Quality of peanut seed oil is influenced by temperature and moisture. However, little is known about the chemical composition of peanut grown in environmental conditions of Turkey. Therefore, this study was conducted at the Cukurova University Farm, Turkey as a main and double cropped to determinate oil quality and fatty acid compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 17 publications
6
31
0
Order By: Relevance
“…Moreover, oil and protein content were decreased in the next cropping seasons of 2014.These results are in partial agreement with the findings of Gulluoglu et al (2016) who found the oil content among peanut varieties was insignificant in main cropped growing season. On the other hand, Islam et al (2016) observed that lower plant population produced the higher percentage of protein and oil content.…”
Section: Oil and Protein Contentsupporting
confidence: 89%
“…Moreover, oil and protein content were decreased in the next cropping seasons of 2014.These results are in partial agreement with the findings of Gulluoglu et al (2016) who found the oil content among peanut varieties was insignificant in main cropped growing season. On the other hand, Islam et al (2016) observed that lower plant population produced the higher percentage of protein and oil content.…”
Section: Oil and Protein Contentsupporting
confidence: 89%
“…Water (Alpaslan et al, 2001) and temperature also influenced the oil content of sesame (Rondanini et al, 2003). Another studies revealed that oil content was influenced under diferent conditions in diferent crops (EL Sabagh et al, 2015Gulluoglu et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained by Mahrous et al (2015) who found that Gregory cultivar showed the highest seed oil content (52.22 %). Also, Gulluoglu et al (2016) found that oil content of peanut cultivars varied between 46.96 and 51.55 % based on dry weight of seeds and the highest oil content value (51.55%) was reported in Georgia Green cultivar, while the lowest one (46.96%) was noticed in Flower-22 cultivar.…”
Section: Seed Quality Determinationmentioning
confidence: 93%